Uso alternativo da terra de diatomácea residual da indústria cervejeira como agregado miúdo na produção de concreto - Sebben, Andrés Alberto (2021)
This work sought to add value to the diatomaceous earth (RTD) residue from the beer filtration stages, using it as a partial substitute for the fine natural aggregate, sand, in the production of conventional non-structural concrete. The methodology evaluated chemically and physically the RTD, as well as other concrete aggregates, followed by the production of concrete samples with four different replacement percentages: C-REF (0%), C-RTD2.5 (2.5%), C-RTF5 (5%), C-RTD10 (10%) of natural fine aggregate by RTD and subsequent analysis of results in its fresh and hardened state, regarding workability, resistance to axial and diametrical compression, modulus of elasticity, mass specific, water absorption and void ratio. The data from this work were evaluated by means of analysis of variance (ANOVA) of a single factor, with 5% significance, and the Tukey-Kramer test was applied to the differences between pairs of concrete mixtures. The results showed that it is possible to use the residue as a partial substitute for sand, however, because it has a high organic load, since it has not undergone any type of treatment, low pozzolanic reactivity and absorption capacity, microscopically justified by its irregular surface and high porosity, all mixtures containing substitutions showed statistically significant differences in relation to the reference mixture. However, analyzing the C-RTD2.5 and C-RTD5 mixtures alone, it is noted that the mechanical differences were not statistically significant, illustrating an acceptable behavior with a replacement limited to 7.5% by mass of the fine aggregate. This study highlights the possibility of using tailings, hitherto without perspective, in the production of concrete without a structural function, and can therefore alleviate the volume of sand extraction and reduce the environmental liability of the brewing industry, thus creating a point alternative point of view for solid waste management and mitigation in the exploitation of non-renewable natural reserves.